Undifferentiated Pancreatic Carcinoma with Osteoclast-like Giant Cells: A Case Report - Jeon, Younghun; So, Hoonsub; Koo, Jaheung; Nah, Yang Won; Lim, Hyunsoo; Kim, Binnari; Lee, Tae Young; Bang, Sung Jo (Korean journal of pancreas and biliary tract, 2023)
Undifferentiated pancreatic carcinoma with osteoclast-like giant cells (UC-OGC) is uncommon, accounting for only 1% of all pancreatic carcinomas. We report a case of a 39-year-old man with undifferentiated pancreatic carcinoma with osteoclast-like giant cells who underwent successful surgical resection and chemotherapy.